Edible mollusc (gastropod and bivalve) at selected divisions of Sarawak - Hamli, Hadi (2013)
Diversity of edible gastropod and bivalve was investigated at seven selected coastal division of Sarawak namely Kuching, Sibu, Mukah, Bintulu, Miri, Limbang and Lawas from July 2010 to January 2012. The most common and widely distributed species i.e., Polymesoda spp. was observed in details for morphology and genetic variation among different populations from different divisions. A total of 41 edible species comprising 11 malacological family of gastropod with 21 species and 12 malacological family of bivalve with 20 species was recorded and identified. Bivalve from Corbiculidae (Polymesoda erosa, P. expansa and P. bengalensis) family was widely distributed in all divisions compared to other bivalve species. Whilst gastropod from Potamididae (Cerithidea obtusa, C. quadrata, C. rizophorarum and Telescopium telescopium) family was commonly recorded at six from seven divisions. Edible species of gastropod and bivalve was found higher in Bintulu division (13 species for gastropod and 11 species for bivalve), while lower number of species was recorded from Sibu and Mukah divisions. Results on Jaccard’s index showed high similarity for edible bivalves within Limbang versus Miri (0.75) and Limbang versus Lawas (0.75), while it was Sibu versus Mukah (0.50) for edible gastropod. This indicated species occurrence between two divisions is almost similar for higher similarity index while different species occurrence for lower similarity index. A total of 15 morphometric characteristics (6 general and 9 additional characters) were used to differentiate three species of Polymesoda recorded from Sarawak. Significant differences (ANOVA, p<0.05) on 12 morphometric characteristics (SL; Shell Length, SW; Shell Width, SH; Shell Height, UL; Umbo Length, AL; Anterior Length, PL; Posterior Length, LPAS; Length of Posterior adductor scar to Anterior adductor Scar, LCT; Length of Cardinal Tooth, PVM; Palial line to Ventral Margin, AAAM; Anterior Adductor scar to Anterior Margin, PAPM; Posterior Adductor scar to Posterior adductor Margin and VPM; Ventral Posterior Margin) were found among three Polymesoda species collected from different divisions. Analysis showed that the proportion ratio for LCT/SL have had significant difference (ANOVA, p<0.05) between P. bengalensis and P. expansa, whilst VPM/SL significantly different (ANOVA, p<0.05) for P. erosa and P. expansa contrasted with P. bengalensis. However, the differences were not significant (ANOVA, p>0.05) between P. erosa and bengalensis, and P. erosa and P. expansa for LCT/SL and VPM/SL respectively. Sixteen populations comprises of P. erosa, P. expansa and P. bengalensis recorded from different divisions were assessed (ANOVA) using morphometric characteristics to reveal differences among the species. Results showed significant differences (p<0.05) among populations of different divisions. Morphometric characteristic analysis on 16 populations of Polymesoda can be grouped based on cluster analysis which resulted in six groups at 98% similarity, namely Group 1 (P. bengalensis population from Limbang, Lawas, Miri, Bintulu and Kuching), Group 2 (P. bengalensis population from Sibu), Group 3 (P. expansa population from Miri and P. erosa population from Lawas and Miri), Group 4 (P. erosa population from Sibu, Mukah and Bintulu), Group 5 (P. expansa population from Limbang, Lawas and Bintulu) and Group 6 (P. erosa population from Limbang). These six groups of Polymesoda population were also supported by the results of Principal Component Analysis (PCA). Genetic distance analysis through the 5S rDNA primer on Polymesoda species (P. erosa, P. bengalensis and P. expansa) revealed distinct banding patterns for 16 population samples from seven divisions (Limbang, Lawas, Miri, Bintulu, Mukah, Sibu and Kuching) of Sarawak. Band size for P. erosa and P. bengalensis were ranged from 100-1000 bp, while P. expansa 100-500 bp. Finding demonstrated that the most distant genetic was P. bengalensis from Bintulu (0.3365) while the close related genetic distance was P. expansa (Miri and Bintulu) and P. bengalensis (Sibu and Kuching) with 0.000 genetic distant. The results highlight the efficiency of 5S rDNA marker as identification tool which consent the identification of Polymesoda species.